2020
DOI: 10.1371/journal.pone.0241494
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of full endoscopic spinal surgery for lumbar disc herniation over a 10-year period: A retrospective study

Abstract: Objective Full endoscopic lumbar discectomy (FELD) for lumbar disc herniation (LDH) has become popular in recent years. Previous studies have proven the efficacy, but few have discussed the possible risk factors of poor outcome. In this study, we reviewed patients who underwent FELD at Changhua Christian Hospital in the past 10 years and sought to identify factors associated with poor surgical outcomes and re-operations. Methods We retrospectively reviewed records from mid-2009 to mid-2018. Patients had unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A prospective study conducted by Dewing et al [ 33 ] showed that younger patients with contained disc herniation had significantly worse outcomes than those with sequestered or extruded herniation. Chen et al [ 16 ] retrospectively reviewed the records of 521 patients who underwent full endoscopic lumbar discectomy, and reported that protrusion was a predictor of poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study conducted by Dewing et al [ 33 ] showed that younger patients with contained disc herniation had significantly worse outcomes than those with sequestered or extruded herniation. Chen et al [ 16 ] retrospectively reviewed the records of 521 patients who underwent full endoscopic lumbar discectomy, and reported that protrusion was a predictor of poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Disc migration was classified into five based on a previous research article[ 1 ]: far-upward (zone 1), near-upward (zone 2), near-downward (zone 3), far-downward (zone 4), and no migration[ 1 ]. The Pfirrmann grading system was used to define the degree of disc degeneration, and the condition was graded from I (normal) to V (most severe)[ 10 18 ]. Lesion localization at the axial plane was classified as central, subarticular, foraminal, and extraforaminal types[ 10 ].…”
Section: Aterials and Methodsmentioning
confidence: 99%
“…The Pfirrmann grading system was used to define the degree of disc degeneration, and the condition was graded from I (normal) to V (most severe)[ 10 18 ]. Lesion localization at the axial plane was classified as central, subarticular, foraminal, and extraforaminal types[ 10 ]. Surgical lumbar levels were divided into the following: T12/L1, L1/L2, L2/L3, L3/L4, L4/L5, L5/S1, L4/L5 + L5/S1, and two levels other than L4/L5 + L5/S1.…”
Section: Aterials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations